The Role of Bleeding History: Mortality Risk Acute Leukimia - Senaputra , Mas Aditya; Ariningrum, Dian; Immakulata Diah Pramudianti, Maria; Ratnani, Daniela; Sidharta, B. Rina Aninda; Eka Rezkita, Bastomy; Putri, Desi Puspa (Poltekkes Kemenkes Surabaya, 2025)
Acute leukemia is a malignant hematological disease with a low survival rate. The survival rate of acute leukemia patients is influenced by several factors, one of which is a history of bleeding. This study aimed to evaluate whether a history of bleeding constitutes an independent risk factor for mortality in patients diagnosed with acute leukemia at Dr. Moewardi Regional General Hospital, Surakarta. This study employed an observational and analytical retrospective cohort design. The subjects were patients diagnosed for the first time with acute leukemia by bone marrow puncture (BMP) and immunophenotyping from January to December 2023. The data was analyzed using chi-square for bivariate analysis and multivariate logistic regression. Survival analysis was performed using the Kaplan-Meier test. A total of 124 patients were included in the analysis. Bivariate analysis demonstrated that both history of bleeding (p = 0.008) and leukocyte count (p = 0.001) were significantly associated with mortality. Multivariate logistic regression confirmed that a history of bleeding (p = 0.027; relative risk [RR] = 3.45) and leukocyte count exceeding 50,000 cells/μL (p = 0.002; RR = 5.10) were independently associated with reduced survival. Kaplan-Meier survival curves showed lower cumulative survival among patients with a history of bleeding and those with elevated leukocyte counts. A history of bleeding is an independent risk factor for decreased survival in patients with acute leukemia at Dr. Moewardi Regional General Hospital. Additionally, leukocyte counts exceeding 50,000 cells/μL are associated with significantly worse survival outcomes.